1973
DOI: 10.1037/h0034549
|View full text |Cite
|
Sign up to set email alerts
|

Second-order effects in mental health treatment.

Abstract: This article argues that mental health clients are typically processed through a fairly standardized, complex professional system which, in its pursuit of salutary "helping" goals may also be occasioning serious, negative second-order effects for its clients. Clinicians have paid little attention to this possibility, and negative second-order effects are thus not typically monitored in therapy or studied in research. The intent of the present article is to direct the professionals' attention to the reasonable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

1977
1977
1996
1996

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…Crisis intervention and subsequent treatment by professionals has occasionally been criticized because of a tendency on the part of many professionals to overuse the formal and all-too-often artificial mental health service delivery system to the exclusion of more natural resources or inherent selfhealing processes (Graziano & Fink, 1973;Himmelsbach, 1974). It should be noted that the professionals in the present study have an orientation toward extensive use of the telephone as an essential preliminary screening device geared to assess resources naturally supportive or helpful to the potential client and to control as precisely as possible entry into the formal mental health service delivery system.…”
Section: Discussionmentioning
confidence: 99%
“…Crisis intervention and subsequent treatment by professionals has occasionally been criticized because of a tendency on the part of many professionals to overuse the formal and all-too-often artificial mental health service delivery system to the exclusion of more natural resources or inherent selfhealing processes (Graziano & Fink, 1973;Himmelsbach, 1974). It should be noted that the professionals in the present study have an orientation toward extensive use of the telephone as an essential preliminary screening device geared to assess resources naturally supportive or helpful to the potential client and to control as precisely as possible entry into the formal mental health service delivery system.…”
Section: Discussionmentioning
confidence: 99%
“…A significant step in the study of service continuance has been the shift in focus from demographic characteristics of the service recipient to service system barriers and pragmatic day-today constraints. Researchers have increasingly focused on barriers related to affordability (Lorefice, Borus, &L Keefe, 1982;Sharfstein & Taube, 1982;Takeuchi, Leaf, & Kuo, 1988); transportation and child care (Margolis & Meisels, 1987;Temkin-Greener, 1986); accessibility (Acosta, 1980;Cohen, 1972;Graziano & Fink, 1973 , 1985); and system characteristics such as the availability of services (Leaf, Bruce, Tischler, & Holzer, 1987;Scott, Balch, & Flynn, 1984;Stefl & Prosperi, 1985), hours of operation and configuration of services (Good, 1990;Margolis & Meisels, 1987;Sledge et al, 1990), and delays in scheduling appointments (Leigh, Ogborne, & Cleland, 1984;Sirles, 1990). Low-income families are particularly challenged by difficulties in meeting basic daily living needs, which can interfere with accessing and continuing in services for their children.…”
Section: Service Continuancementioning
confidence: 99%
“…In this regard Fiester, Mahrer, Ciambra, and Ormiston (1974) indicated that clients who unilaterally terminate therapy have a greater incidence of therapist-adjudged need for further care. Graziano and Fink (1973) stated strongly, "It seems clear that for the majority of people who seek help, the treatment process is a decided failure" (p. 362).…”
Section: Iilimb Department Of Mental Healthmentioning
confidence: 99%
“…He/she may have received appropriate assistance, may have found alternative resources, or may have been exposed to environmental factors which changed or alleviated the need for intervention. In addition, the decision to terminate may be a functior, of second-order factors not easily controlled by either the client or the intervention system, e.g., scheduling difficulties, financial arrangements, and transportation (Graziano & Fink, 1973). In this regard Garfield (1963) indicated that over half of the dropout clients he studied gave reasons external to the therapeutic encounter for leaving, e.g., babysitting, no transportation.…”
Section: Iilimb Department Of Mental Healthmentioning
confidence: 99%